(untitled) (Research, Society and Development, 2022)
Oenocarpus distichus is a palm tree that is a refreshment called “bacaba”, very appreciated by traditional communities in the state of Pará. It has multiple uses, may be using in landscaping projects, in the production of herbal medicines, among others. However, there is a lack of agronomic information about the referred species, as well as the management strategies. The present research aimed to quantify the genetic divergence in provenances of O. distichus of the Pará based on morphoagronomic characters. Fifteen characters was measured, three relating to the plant, four to the bunch and eight to the fruit, in 62 individuals from four sources: twelve from Marabá, thirty from Belém, twelve from São João do Araguaia and eight from Baião. Data were submitted to uni and multivariate analyses, the latter using the Euclidean distance, the formation of groups using the complete linkage method, and the importance and discarding of characters based on the principal components. The greatest divergence was found between two individuals from Belém, BEL-11 and BEL-8 (dii’= 13.69). There was the formation of seven distinct groups. The characters weight of one hundred fruits and the number of rachiles per bunch were show to have the greatest contribution to the divergence between provenances. The first three main components concentrated 66.16% of the accumulated variance, and the fruit characters were responsible for the variation of individuals, suggesting that two of them were discard: circumference at breast height and length of the central rachis. Individuals of O. distichus from the four provenances of Pará studied show considerable phenotypic variation for the morphoagronomic characters studied, mainly for the fruit characters, with those from Marabá being more divergent among the four provenances.